ἀπονέμοντες τιμήν: 1 Peter as subversive text, challenging predominant gender roles in the 1st-century Mediterranean world - Roux, Elritia Le (HTS teologiese studies, 2019)
Although the tension which Christianity, in continuance with the Sache Jesu, first displayed with its surrounding culture, gradually conformed to the predominate culture of the ancient Mediterranean world, probably to avoid further conflict, it seems that the author of 1 Peter, despite my preference for a later dating (circa the turn of the 1st century AD), was set on maintaining this tension. 1 Peter employs a ‘revolutionary subordination’. When the author of 1 Peter urges wives to be submissive or slaves to obey their masters, he is not perpetuating normative conservatism. Rather, wives and slaves as followers of Christ were to subvert injustice the same way Jesus did. Wives therefore do not submit to their non-believing husbands because they buy in to society’s evaluation of them as inferior to their male counterparts. Rather, wives can submit to their non-believing husbands because they are triumphant in Christ and therefore emancipated moral agents, who may win over their non-believing husbands by their moral and godly conduct.